A high-precision instrument for mapping of rotational errors in rotary stages - Xu, Weihe (Journal of synchrotron radiation, 2014)
A rotational stage is a key component of every X-ray instrument capable of providing tomographic or diffraction measurements. To perform accurate three-dimensional reconstructions, runout errors due to imperfect rotation (e.g. circle of confusion) must be quantified and corrected. A dedicated instrument capable of full characterization and circle of confusion mapping in rotary stages down to the sub-10 nm level has been developed. A high-stability design, with an array of five capacitive sensors, allows simultaneous measurements of wobble, radial and axial displacements. The developed instrument has been used for characterization of two mechanical stages which are part of an X-ray microscope